Harmonisation of ethics committees' practice in 10 European countries. Issue 11 (30th October 2009) - Hernandez, R; Cooney, M; Dualé, C; Gálvez, M; Gaynor, S; Kardos, G; Kubiak, C; Mihaylov, S; Pleiner, J; Ruberto, G; Sanz, N; Skoog, M; et al.
Abstract : Background: The Directive 2001/20/EC was an important first step towards consistency in the requirements and processes for clinical trials across Europe. However, by applying the same rules to all types of drug trials and transposing the Directive's principles into pre-existing national legislations, the Directive somewhat failed to meet its facilitation and harmonisation targets. In the field of ethics, the Directive 2001/20/EC conditioned the way of understanding and transposing the "single opinion" process in each country. This led to a situation in which two models of research ethics committees organisation systems exist, being the model in which the "single opinion" is considered to be the decision made by a single ethics committee more effective and simpler in terms of administrative and logistic workload. Method: A survey was conducted in 10 European countries. Members of the European Clinical Research Infrastructures Network working party number 1, with expertise in the field of ethics, responded. Results: There is a major heterogeneity in the composition of ethics committees among the surveyed countries based on the number of members, proportion of experts versus lay members and expertise of the scientific members. A harmonised education of the ethics committees' membership based in common curricula is recommended by the majority of countries. Conclusions: Despite the efforts for harmonisation of the European Clinical Trial Directive, from an ethical point of view, there remains a plurality of ethics committees' systems in Europe. It is important to comprehend the individual national systems to understand the problems they are facing.